Maternal HIV infection and preeclampsia increased risk of low birth weight among newborns delivered at University of Gondar specialized referral hospital, Northwest Ethiopia, 2017 - Daniale Tekelia Ekubagewargies; Destaye Guadie Kassie; Wubet Worku Takele (BMC, 2019)
Abstract Introduction Globally, more than 20 million infants are born with low birth weight. The risk of neonatal mortality among low birth weight infants is 25 to 30 times greater than neonates with birth weight ≥ 2500 g. Low birth weight infants are at increased risk of infection, difficulty of feeding, and neurologic problems following birth. So far, the prevalence and factors associated with low birth weight have not been studied in the study area after completion of the time set for millennium development goals. Therefore, the study was aimed at assessing the prevalence and associated factors of low birth weight among newborns delivered at University of Gondar specialized referral hospital, Northwest Ethiopia, 2017. Methods Institution-based retrospective cross-sectional study was conducted from April 1 to May 28, 2017. A total of 240 newborns were included in the study. Systematic random sampling technique was used for selecting study participant's medical record charts from delivery registration log book. Data were collected using data extraction tool. Binary logistic regression followed by multivariable regression model was fitted and interpretation was made based on the adjusted odds ratio and p-value of less than 0.05 with corresponding 95% CI. Results The prevalence of low birth weight was 12.9% (95%CI: 8.94, 17.83%). No history of preeclampsia (AOR = 0.193, 95%CI: 0.0516, 0.723), negative maternal HIV infection (AOR = 0.015, 95%CI: 0.001, 0.277), and being preterm (AOR = 17.6, 95%CI: 5.18, 60.17) were significantly associated with low birth weight. Conclusion and recommendations The result of this study highlighted that the burden of low birth weight is a public health concern among babies delivered in University of Gondar specialized referral Hospital. Maternal HIV infection, preeclampsia, and prematurity were associated with low birth weight. Prevention and treatment of Human immunodeficiency virus infection during pregnancy, tackling prematurity and prevention of preeclampsia through strengthening of antenatal care service and other comprehensive strategies are strongly recommended.